THE EVALUATION OF SUSTAINABLE TOURISM VILLAGES THROUGH MANAGEMENT STRUCTURE AND FRAMEWORK IN SURABAYA CITY - Sucipto Sucipto; Siti Nuurlaily Rukmana (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
Sustainable tourism development has become a positive trend in every region, especially in densely populated urban areas. Surabaya is one of the cities that has shown special attention to the development of sustainable villages through the tourism sector. Since 2005, Surabaya City has implemented a green village policy or program to realize Surabaya Green and Clean. The paper focused on discussing sustainable tourism villages through the existing structure and management framework in Surabaya City. The method used in this paper was descriptive evaluative with triangulation data wetness techniques in tourist villages in Nginden Village, Surabaya. The results of the evaluation of the structure and management framework of Kampong Herbal Nginden Surabaya have an evaluation result of 92% which is oriented as a smart village because it is used as a forum for learning communities.